Preventing new episodes of bipolar disorder in adults: Systematic review and meta-analysis of randomized controlled trials - Nestsiarovich, Anastasiya; Gaudiot, Christopher E.S.; Baldessarini, Ross J.; Vieta, Eduard; Zhu, Yiliang; Tohen, Mauricio (European neuropsychopharmacology, 2022)
Uncertainty remains regarding the relative efficacy of maintenance pharmacotherapy for bipolar disorder (BD), and available data require updating. The present systematic review and meta-analysis aims to consolidate the evidence from the highest quality randomized controlled trials (RCTs) published up to July 2021, overcoming the limitations of earlier reviews. The PubMed and the Cochrane Central Register of Controlled Trials were searched for double-blind RCTs involving lithium, mood stabilizing anticonvulsants (MSAs), antipsychotics, antidepressants, and other treatments. Rates of new mood episodes with test vs. reference treatments (placebo or alternative active agent) were compared by random-effects meta-analysis. Polarity index was calculated for each treatment type. Eligible trials involved ≥6 months of maintenance follow up. Of 2,158 identified reports, 22 met study eligibility criteria, and involved 7,773 subjects stabilized for 1–12 weeks and followed-up for 24–104 weeks. Psychotropic monotherapy overall (including lithium, MSAs, and second generation antipsychotics (SGA) was more effective in preventing new BD episodes than placebo (odds ratio, OR=0.42; 95% confidence interval, CI 0.34–0.51, p<0.00001). Significantly lower risk of new BD episodes was observed with the following individual drugs: aripiprazole, asenapine, lithium, olanzapine, quetiapine, and risperidone long-acting (ORs varied 0.19–0.46). Adding aripiprazole, divalproex, quetiapine, or olanzapine/risperidone to lithium or an MSA was more effective compared with lithium or MSA monotherapy (OR=0.37; 95%CI 0.25–0.55, p<0.00001). Active treatment favored prevention of mania over depression. The key limitations were “responder-enriched” design in most trials and high outcomes heterogeneity. PROSPERO registration number is CRD42020162663.